2001
DOI: 10.1136/bjo.85.7.792
|View full text |Cite
|
Sign up to set email alerts
|

Central corneal thickness measurements in patients with normal tension glaucoma, primary open angle glaucoma, pseudoexfoliation glaucoma, or ocular hypertension

Abstract: Background/aims-Recent studies have revealed patients with ocular hypertension to have thicker than normal central corneas and those with normal tension glaucoma to have thinner than normal ones, as determined by ultrasonic pachymetry. Since corneal thickness measurements and applanation tonometric estimates of intraocular pressure (IOP) correlate positively, monitoring of the former parameter have served as the basis for adjusting readings pertaining to the latter, with the consequence that many patients have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
5
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 24 publications
10
73
5
10
Order By: Relevance
“…Detorakis et al (11) reported that differences in CCT between PXS eyes and age-and sex-matched controls were not statistically significant. Ventura et al (12) and Yagci et al (13) reported that there were no significant differences in CCT among normal-tension glaucoma, primary open-angle glaucoma, pseudoexfoliative glaucoma, and healthy control groups. However, Gorezis et al (14) found that the CCT was significantly thinner in patients with pseudoexfoliative glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detorakis et al (11) reported that differences in CCT between PXS eyes and age-and sex-matched controls were not statistically significant. Ventura et al (12) and Yagci et al (13) reported that there were no significant differences in CCT among normal-tension glaucoma, primary open-angle glaucoma, pseudoexfoliative glaucoma, and healthy control groups. However, Gorezis et al (14) found that the CCT was significantly thinner in patients with pseudoexfoliative glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are conflicting studies about central corneal thickness (CCT) in patients with PXS or pseudoexfoliative glaucoma. Most studies have reported similar CCT in PXS and normal eyes (9)(10)(11)(12)(13) , but some authors have reported a thinner (14,15) or thicker (16,17) CCT in PXS eyes than in normal eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, true IOP, and therefore glaucoma risk, may be underestimated in these eyes. This may explain the findings that mean CCT is thinner in patients with normal tension glaucoma compared with those having POAG, 6,7 and thicker in patients with OHT. 8,9 These findings are replicated among different racial groups.…”
Section: Introductionmentioning
confidence: 92%
“…Optical low coherence reflectometry represents the most precise pachymetric method available, with its measurements reproducible to 1 µm. 12 In the future, appropriate refinement of the correction formula may need to be undertaken, depending on the corneal pachymetric method adopted.…”
Section: Discussionmentioning
confidence: 99%